UNDERSTANDING TURNOVER INTENTION FACTOR THROUGH RECRUITMENT SYSTEM IN STUDENT ORGANIZATION CASE STUDY: PADUAN SUARA MAHASISWA (PSM) ITB - Maniani, Hilda; Lantu, Donald Crestofel (Journal of Business and Management, 2017)
Abstract. Institut Teknologi Bandung is one of the institution in Indonesia that provide a student organization to help their student increasing their social life. There is an oldest choir organization student; it is Paduan Suara Mahasiswa (PSM) ITB.  They already get many achievements in national and international level. It make them famous student organization in ITB, that is why the applicant that registered in PSM-ITB can achieve 300 applicant every year. However, there is high member turnover in PSM-ITB every year. Turnover intention can be caused by various reason; further research said that individual have a key role in desire to remain the job. It make human resource management practices take a part of the turnover intention. Nevertheless, from the entire human resource management practices, the root the psychological contract that effect the turnover intention is recruitment system (Rousseau, 1994). Recruitment system  have four factor that affect the successfulness, it is source distribution, new hire quality, time to fill and cost per hire. Purpose of this research is to understand the factor in recruitment system that related with the turnover intention in PSM-ITB. This research is using qualitative approach. For the analysis researcher using thematic framework. The result of this research will show the factor that affect the recruitment system in PSM-ITB that related with the turnover rate. Keywords:  Human Resource Management Practices, Psychological Contract, Paduan Suara Mahasiswa (PSM) ITB, Recruitment System, Turnover Intention